ANALISIS TRAFFIC LIGHT JALAN CINDE KEDUNGMUNDU SEMARANG - Sulistyo, Juny Andry (Pondasi, 2023)
One of the main indicators of the development progress of a region or city is transportation; Cities that have good transportation services will become developed. The aim of this research is to measure intersection performance based on the degree of saturation, delays and queue length, as well as to find out how the intersection functions during peak hours.The 1997 Indonesian Road Capacity Manual is used as a reference for assessing intersection performance. This study uses a quantitative methodology with direct research in the field. CCTV cameras and Go-Pro cameras are used as analytical tools in the field.According to research conducted at Simpang Jalan Cinde, the value of the degree of saturation at the Jalan Army Student - Kedung Mundu intersection is 0.61 for the southern approach, 0.51 for the western approach, and 0.51 for the eastern approach.